FAKTOR - FAKTOR YANG MEMPENGARUHI TERJADINYA KECURANGAN (FRAUD) PADA PENGADAAN BARANG DAN JASA DI KABUPATEN PELALAWAN (Studi Empiris Pada Kabupaten Pelalawan) - Gusnita, Jumeilia; Hasan, Amir; Rasuli, M. (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2019)
This study aims to examine the influence of factors such as Quality of Procurement of Goods / Services Committee, Procurement of Goods / Services Environment, Income of Procurement of Goods / Services Committee, Procurement of Goods and Services System and Procedure, Procurement of Goods / Services Ethics, to Fraud in Procurement of Goods / Services to Pelalawan Government Agencies and test whether there are differences in assessment between Respondents of Internal Agencies and BPKP Auditors.The results of the study indicate that both simultaneous / combined tests are carried out in whole / combined and separately, it is known that the Quality of Procurement Committees, Procurement Committee Procurement, Procurement System and Procedure, Procurement Ethics, and Procurement Environment simultaneously have a significant effect on fraud in the procurement of goods / services to Pelalawan Government Agencies. Lastly, the tests carried out as a whole / combined all variables have a positive effect on fraud in the process of procurement of goods / services. Whereas if the test is carried out separately, based on respondents from internal parties, all independent variables significantly influence the dependent variable. Referring to previous research research methods that use questionnaires still cannot explain the factors that influence fraud in the procurement of goods / services more "blurred". The real difference between the results of this study with previous research, confirms that the practice of fraud / fraud in each of the different scopes will produce different results.